Efficiency of mechanical extraction of Moringa oleifera according to different grain drying conditions (Research, Society and Development, 2020)
Moringa oleifera Lam. is a drought-resistant plant and able to survive in poor soils, obtaining up to three harvests per year. This culture has wide employability in the cosmetics, medicinal, food industry and also as a potential for water purification. Despite its widespread use, there are few studies on its processing. Thus, the objective of this work was to study the behavior during the drying process, at the drying air temperatures of 40 ºC, 55 ºC and 70 ºC, applying mathematical models to the experimental data, thus selecting the best model according to the kinetics curves of drying, as well as evaluating the effect of this phenomenon on the efficiency of mechanical oil extraction. Pre-dried Moringa oleifera Lam. grains from the city of Barreirinhas (MA) were used, the second semester of 2018 and the experiment conducted at the Agricultural Engineering Department of the Federal University of Lavras (MG). Artificial drying was carried out to a constant grain mass, using a mechanical laboratory dryer in a fixed layer with forced convection, at an air speed of 0.33 ms-1, with controlled drying air temperatures of 40 °C, 55 °C, and 70 °C. Non-linear regression analysis was performed using the Quasi-Newton method to adjust 11 mathematical models to experimental data. The oil was extracted using an expeller-type mechanical press. The press yield and efficiency were calculated from the difference in lipid content obtained by the initial chemical extraction of the grain and residual of the pie. The Exponential Equation of Two Terms was the one that best suited the experimental data for all drying air temperatures. The increase in the temperature of the drying air caused greater volumetric contraction of the moringa grains, which affected the oil extraction yield, resulting in lower efficiency of the mechanical press.